Influence of Social Media on Body Image & Fashion Trends among Youth - Yunus, Asma; Muhammad Tahir; Dr. Shuja Ur Rehman (Journal of Peace, Development and Communication, 2023)
This article focuses on the effects of electronic media on fashion trends and body image of youngsters in higher educational institutions of Pakistan. This study explains the contribution of various mass media sources as a strong agent of non-formal socialization to reshape the youth behavior in terms of their tendencies on fashion and image of human body. The present study is a quantitative in nature. In this study, 329 students were taken as respondents from the tertiary level educational institutions of Khyber Pakhtunkhwa and Gilgit Baltistan, Pakistan. The data has been obtained through a structured questionnaire and analyzed through chi-square test to know the association between popular media sources and fashion trends and body image. Body image concerns in youth behavior (P=.000). Responses taken in this study shows the TV and social Media are catalyst which determines the career plans of youth. This study further found that electronic and social media are persuasive sources of communication among masses that has vital effects on the youngsters and it remakes their behavior. This behavior actually influences their behavior that what to eat, drink, smoke, wear and use or buy from market. This research may contribute to social psychology and sociology of media and communication. This article recommends that keeping in view the contemporary needs of electronic media has to design such programs to convey desirable information, content and reality to masses so that can be more trustworthy, valid and reliable.